2023
DOI: 10.1111/obr.13670
|View full text |Cite
|
Sign up to set email alerts
|

Association of bariatric surgery with indicated and unintended outcomes: An umbrella review and meta‐analysis for risk–benefit assessment

Min Seo Kim,
Jong Yeob Kim,
Yong Shin Song
et al.

Abstract: SummaryBariatric surgery can cause numerous functional changes to recipients, some of which are unintended. However, a systematic evaluation of wide‐angled health benefits and risks following bariatric surgery has not been conducted. We systematically evaluated published systematic reviews of randomized controlled trials and observational studies reporting the association between bariatric surgery and health outcomes. We performed subgroup analyses by surgery type and sensitivity analysis, excluding gastric ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Several studies documented that the prevalence of suicidal ideation or depressive symptoms increases with BMI [ 34 , 35 , 38 , 39 ]. However, due to BMI's limitations, including its inability to differentiate between excess fat, muscle, or bone mass, and its failure to discern body fat distribution across different locations, some studies are beginning to experiment with other indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies documented that the prevalence of suicidal ideation or depressive symptoms increases with BMI [ 34 , 35 , 38 , 39 ]. However, due to BMI's limitations, including its inability to differentiate between excess fat, muscle, or bone mass, and its failure to discern body fat distribution across different locations, some studies are beginning to experiment with other indicators.…”
Section: Discussionmentioning
confidence: 99%
“…The current data indicate that the perioperative mortality rates of BST range from 0.03% to 0.2%, which has substantially improved since the early 2000s [8,9]. A recent review of 66 health outcomes of bariatric surgery has shown that 56 outcomes were health benefits, including new-onset of diabetes, dyslipidemia, cardiovascular diseases, hypertension, cancers, women's health, and reductions in all-cause mortality and 10 were adverse outcomes, including suicide, fracture, gastroesophageal reflux after sleeve gastrectomy, and neonatal morbidities, but none of the adverse outcomes reached a high level of evidence, warranting the need for further investigation.…”
Section: Introductionmentioning
confidence: 92%
“…However, Nutrients 2024, 16, 1466 2 of 13 emerging evidence suggests that the sleeve procedure is associated with fewer reoperations, and the bypass procedure may lead to more durable weight loss and glycemic control. Different types of bariatric surgery have distinct auxiliary and adverse effects, emphasizing the importance of individualized selection of procedures and risk-benefit conversations for each patient considering bariatric surgery [8,9].…”
Section: Introductionmentioning
confidence: 99%